Using numbers 1 3 5 7 9 11 13 17 19 in 5 steps sum should be 30.We can repeat numbers.

Answers

Answer 1
Answer: All given numbers are odd. The sum of odd number (in this case 5) of such numbers is odd too. 30 is an even number, so it's impossible to get 30 in total by adding up any of these numbers.

Related Questions

The following are angles in a convex quadrilateral: Angle A = 34 degrees Angle B = 108 degree Angle C = 65 degrees What is the measure of the missing angle?
Find the square. (6m+7)2
Josh baked 13 dozen apple muffins and 25 dozen blueberry muffins.About how many muffins did he make?
Tulio Fernandez purchased a treadmill with an installment loan that has an APR of 12%. The treadmill sells for $1,672. The store financing requires a 10% down payment and 12 monthly payments. What is the finance charge?
The ordered pair (2, 36) is a solution for which equation(s)? Check all that apply. A. y = (x + 4)2B. y = 7x2 + 2C. y = (3x)2D. y = 2x2

What is the standard deviation of the mean change in score for the students who paid a private tutor to help them?

Answers

Answer:

a, b

Step-by-step explanation:

You earn 21.00 per hour at your job if you get a 9% raise at the end of each year what wil your hourly rate be after 5 years

Answers

At the end of 5 years, you will get a 9.45 dollar raise

21.00*.09=1.89
1.89*5=9.45

so 21.00+9.45= 30.45
Year 1 $22.89
Year 2 $24.95
Year 3 $27.20
Year 4 $29.65
Year 5 $32.32

can you write an equation by setting an expression equal to itself. would an equation like this be true

Answers


Of course !  An expression is always equal to itself.

But if there's, say, an 'x' in the expression, then such an equation would be true
for x=every possible number.  You might say it has an infinite number of solutions ...
which certainly has to be true, because no matter what you do to an expression,
it's still always equal to itself !

 
yes it would be as long as it truly equals eachother

Greatest common factor of 126

Answers

Answer:

1

Step-by-step explanation:

How to find the diagonals of a parallelogram?

Answers

Well you draw a diagonal line across the parallelogram and then do the pythogorean theroem with the base and height and you'll have the hypotenuse/diagonal

Which linear system has the solution (6, 6)A:4x - 3y = -1 -2x + y = -3
B: x + y = 12 3x - 2y = 6
C: 3x + y = 4 4x - 3y = 1
D: 4x + 3y = 0 2x - y = 0

Answers

B: x+y=12 3x-2y=6
6+6=12 (3×6)-(2×6)=6
By substituting x = 6 and y = 6 into the options we have that the correst answer is option B.